Problems of Interests and Attitudes of Students in Special Regions towards Science Subjects - Reni Marlina; Hadi Suwono; Ibrohim; Haratua Tiur Maria Silitonga; Erwina Oktavianty; Hamdani (Research Highlights in Language, Literature and Education Vol. 4, 2023)
The goal of this study is to determine the relationship between students’ interests and attitudes as a result of differences in the pedagogical and professional competence of teachers in specific regions. The concepts examined are science concepts from grades 7 and 8. This study used a comparative causal method with the number of samples involving 109 students consisting of 3 school levels, namely the upper, middle, and lower group schools with 2 schools respectively. There were six teachers in special regions involved as participants, each of whom comes from the schools in the 3T (least developed, frontier, and outermost) regions. The collected data were examined using a non-parametric scale method and a single sample of the Chi-Square statistical test. According to the findings of the statistical tests, which had dk = 2 and a = 0.05, it was determined that the teachers had a high degree of pedagogical and professional proficiency. Teachers’ pedagogical and professional competence contributed positively to students’ interest and attitude toward scientific concepts. Furthermore, this study discovered that the contribution of teachers’ pedagogical and professional competence to the student’s interest and attitude fell into a high category in science concepts and students had a strong interest in science concepts (57%) contained in the curriculum. In light of this, it can be said that a teacher’s high level of pedagogical and professional competence positively affects the interest and attitude of pupils toward science topics.